HUKUM PERDATA PROGRESIF: PERUBAHAN DAN KESINAMBUNGAN PENEMUAN HUKUM DI BIDANG HUKUM PERDATA - Hidayat, Maskur (Jurnal Hukum dan Peradilan, 2014)
Law is a tool that people can achieve order and the protection of basic human rights. Among others, the right to life and protection, both physical protection, protection of honor and decency and the protection of property rights or properties. The phrase that nothing is eternal except change undoubtedly also applies in the legal world. Every moment is always evolving human problems, as well as a method of conflict resolution must also keep abreast of developing issues. Became law at the center of media demands, namely the rule of law and sense of justice. On the side of the rule of law, justice demands that can be placed exactly over the other side into a sense of justice also demands that require judges to give a personal touch (case by case) in the face of any problems encountered in the trial. Keywords: rule of law, justice and progressive law.